International handbook of leadership for learning - Townsend, Tony.; MacBeath, John.; SpringerLink (Online service). (Dordrecht Springer Netherlands, 2011)
The International Handbook of Leadership for Learning brings together chapters by distinguished authors from thirty-one countries in nine different regions of the world. The handbook contains nine sections that provide regional overviews; a consideration of theoretical and contextual aspects; system and policy approaches that promote leadership for learning with a focus on educating school leaders for learning and the role of the leader in supporting learning. It also considers the challenge of educating current leaders for this new perspective, and how leaders themselves can develop leadership for learning in others and in their organisations, especially in diverse contexts and situations. The final chapter considers what we now know about leadership for learning and looks at ways this might be further improved in the future. The book provides the reader with an understanding of the rich contextual nature of learning in schools and the role of school leaders and leadership development in promoting this. It concludes that the preposition ?for? between the two readily known and understood terms of leadership and learning changes everything as it foregrounds learning and complexifies, rather than simplifies, what that word may mean. Whereas common terms such as instructional leadership reduce learning to outcomes, leadership for learning embraces a much wider, developmental view of learning. - publisher's description.
Part One.- PREFACE.- 1. Leadership and learning: paradox, paradigms and principles; John MacBeath and Tony Townsend.- SECTION 1: MAJOR THEMES IN LEADERSHIP FOR LEARNING: AN INTERNATIONAL PERSPECTIVE.- 2. U.S. Cultural History: Visible and Invisible Influences on Leader-ship for Learning; Ira Bogotch.- 3. Leadership for Learning in Canada; Larry Sackney.- 4. Leadership for Learning in Latin America; Beatrice Avalos.- 5. Trans-national and local conditions and expectations on school leaders; Lejf Moos.- 6. Leadership for Learning in the UK; Jim O?Brien.- 7. Leadership and Learning: Making Connections Down Under; Neil Dempster.- 8. Leadership for Learning in the Middle East; Thuwayba Al-Bawani.- SECTION 2: THEORETICAL AND CONTEXTUAL FRAMEWORKS FOR LEADERSHIP FOR LEARNING.- 9. Researching Leadership: Towards a new Paradigm; Daniel Muijs.- 10. A Multi Faceted Perspective on Leadership for Learning: A Case Study of Morocco; Abdelkader Ezzaki.- 11. Leadership for Learning: Research Findings and Frontiers from Down Under; Neil Dempster, Greg Robson and Mike Gaffney.- 12. A Developmental Framework for Instructional Leadership; Ulrich C. Reitzug and Deborah L. West.- SECTION 3: SYSTEM AND POLICY ISSUES ON LEADERSHIP FOR LEARNING.- 13. Quality and Accountability: policy tensions for Australian school leaders; Sue Thomas and Louise Watson.- 14. Leadership for Learning in China: The Political and Policy Context; Qian Haiyan and Allan Walker.- 15. Transforming Singapore Schools ?The Economic Imperative, Government Policy and School Principalship; Clive Dimmock and Jonathan Goh.- 16. Internal and External Accountability: Building Evidence-Informed Leadership Capacity at all System Levels; John Burger, Anna Nadirova, Jim Brandon, Bob Garneau and Chris Gonnet.- 17. Developing Leaders, Building Networks, Changing Schools through System Leadership; Wilfried Schley and Michael Schratz.- 18. School leadership in Chile: Breaking the Inertia; José Weinstein, Gonzalo Muñoz and Dagmar Raczynski.- 19. School Leadership in the UK: A Policy Perspective; Jim O?Brien.- SECTION 4: EDUCATING SCHOOL LEADERS FOR LEADERSHIP FOR LEARNING.- 20. Lessons About Improving Leadership on A Large Scale: From Ontario?s Leadership Strategy; Kenneth Leithwood, Steven Reid, Laurie Pedwell, and Marg Connor.- 21. Leadership for learning: educating educational leaders; Christine Forde.- 22. Leadership Learning that Makes a Difference in Schools: Pushing the Frontier at the University of Maine; Richard H. Ackerman, Gordon A. Donaldson, Sarah V. Mackenzie and George F. Marnik.- 23. Educating leaders for learning in schools in Kenya: The need for a re-conceptualisation; Julius O. Jwan and Charles O. Ong?ondo.- 24. Leadership for Learning in Malaysian Schools; Tie Fatt Hee.- 25. Developing school principals in South Africa; Inbanathan Naicker.- 26. Preparing School Leaders for a Changing World: Lessons from Zimbabwe; Chrispen Chiome.- SECTION 5: IMPLEMENTING LEADERSHIP FOR LEARNING: THE ROLE OF THE SCHOOL LEADER.- 27. Collaborative Leadership and School Improvement: Understanding the Impact on School Capacity and Student Learning; Phil Hallinger and Ronald Heck.- 28. Culturally Relevant Leadership for the Enhancement of Teaching and Learning in Urban Schools; Carlos R. McCray and Floyd D. Beachum.- 29. Expanding Learning-focused Leadership in US Urban Schools; Bradley S. Portin and Michael S. Knapp.- 30. The Nordic superintendents? leadership roles: cross national comparisons; Olof Johansson, Lejf Moos, Elisabet Nihlfors, Jan Paulssen and Mik Risku.- 31. Successful leadership for improved student learning in high needs schools: U.S. perspectives from the International Successful School Principalship Project (ISSPP); Stephen Jacobson and Lauri Johnson.- 32. Improving and supporting principals? leadership in Latin America; Denise Vaillant.- SECTION 6: CHANGING HEARTS AND MINDS: BUILDING LEADERSHIP FOR LEARNING IN CURRENT SCHOOL LEADERS.- 33. The Succession Challenge: Warm Bodies or Leaders of Learning?; Dean Fink.- 34. Building Leadership Capacity Across 5000 Schools; Laurie Pedwell, Ben Levin, Barry Pervin, Mary Jean Gallagher, Marg Connor and Helen Beck.- 35. Building leadership capacity ? the Norwegian approach; Jorunn Møller and Eli Ottesen.- 36. Leadership for Learning - Learning for Leadership: The Impact of Professional Development; Stephan Gerhard Huber.- 37. The development of leadership capability in a self-managing schools system: the New Zealand experience and challenges; Cathy Wylie.- 38. Providing professional sustenance for leaders of learning ? the glass half full?; Simon Clarke and Helen Wildy.- 39. Support for schools and professional development: key processes for effective leadership in school improvement; Inés Aguerrondo and Lea Vezub.- Part Two.- SECTION 7: SPREADING THE TASK: INCLUDING OTHERS IN LEADERSHIP FOR LEARNING.- 40. Leadership for Learning: What It Means for Teachers; Susan Lovett and Dorothy Andrews.- 41. Instructional Supervision, Coherence, and Job embedded Learning; Sally J. Zepeda.- 42. School Leadership for Adult Development: The Dramatic Difference It Can Make; Ellie Drago-Severson.- 43. Accomplished Teachers as Teacher Leaders; Margery McMahon.- 44. Ensuring staff development impacts on learning; Sara Bubb and Peter Earley.- 45. Realities and perspectives arising from professional development to improve the teaching of reading and writing: the CETT Project in the Dominican Republic; Liliana Montenegro.- 46. Leadership for Learning: Student Perspectives; James Skinner, Alf Lizzio and Neil Dempster.- 47. Promoting Students Learning through Sustainable Innovations: Where is the missing link?; Thuwayba Al-Bawani and Mohammed Osman.- 48. Creating participative learning cultures through student leadership; David Frost.- SECTION 8: FROM PEOPLE LEARNING TO ORGANISATIONAL LEARNING: BUILDING CAPACITY.- 49. Schools as Organizational Connectors and Reproducers of the Hierarchy of Learning Success; Fenwick English.- 50. Leading school based networks and collaborative learning: Working together for better outcomes?; Mark Hadfield and Christopher Chapman.- 51. Principals think organisation: Dilemmas in the management of today?s education; Peter Henrik Raae.- 52. The Self-Organizing School Theory: Leading change for learning; Alan Bain.- 53. Building and Leading Within Learning Ecologies; Coral Mitchell and Larry Sackney.- 54. Leaders Who Build and Sustain Passion for Learning: Capacity Building in Practice; Qing Gu.- 55. Creating a Learning Culture in Schools: An Analysis of Challenges and Opportunities with Special Reference to the Egyptian Context; Atta Taha Zidan.- 56. Educational leadership with eyes and hearts wide open; Grzegorz Mazurkiewicz.- 57. Leading Assessment for Learning; Sue Swaffield.- SECTION 9: RESPONDING TO DIVERSITY: DIFFERENT WAYS OF MOVING TOWARDS LEADERSHIP FOR LEARNING.- 58. Education leaders can reduce educational disparities; Russell Bishop.- 59. Same mother, different lives: The social organization of leader-ship for learning across three Chinese societies; Allan Walker and Frank Xue-Ju Wang.- 60. Assessing and Understanding Quality in the Arab Region; Ekhleif Tarawneh.- 61. Administrative Approaches to Diversity: Sharing and Imposing Meaning; James Ryan.- 62. Zimbabwe in Transition: Rethinking the school leadership condi-tions fostering transition; Chrispen Chiome and Paul Mupa.- 63. Findings in translation: negotiating and leading learning across borders; Francesca Brotto.- 64. School culture and pupil performance: Evidence from Lesotho; Vitallis Chikoko and Tantso Rampai.- 65. Re-Imagining Disadvantaged Community and Family Leadership for Learning: An (Im)modest Proposal; Greer Johnson & Paula Jervis-Tracey.- AFTERWORD.- 66. Thinking and Acting both Locally and Globally: What do we know now and how do we continue to improve?; John MacBeath and Tony Townsend.- About the Contributors.- Author Index.- Subject Index.
Electronic reproduction.
Keywords: Educational leadership -- Handbooks, manuals, etc; Leadership -- Handbooks, manuals, etc; Electronic books